Who by Fire: Models of Ideal Femininity in Pre-Modern Tamil Literature - Peres, Ofer (Religions of South Asia, 2021)
The Pururava-caritai (‘The Adventures of Pururavas’) is an unstudied sixteenth-century Tamil adaptation of the famous Vedic legend of Pururavas, which introduces an extensive addition to the original story. One episode within this supplement narrates a trial by fire gone through by the protagonist’s wife, which draws heavily on a similar episode from the Ramayana epic, both in Valmiki’s classical Sanskrit version and in Kampan’s twelfth-century Tamil retelling. This article sheds new light on the ways in which classical literary gender roles and gender models were reimagined in premodern south India. I argue that the re-articulation of the epic fire-ordeal in the Pururava-caritai is a critical reflection on the feminine model that the Ramayana heroine, Sita, represents. I show that, through a synthesis of classical and folk motifs, the author has created an implicit intertextual dialogue that concludes with a complex matrix of values of ‘proper’ femininity and ‘true’ divinity.